COMMUNICATIVE LANGUAGE TEACHING IN SPEAKING CLASS IN ONE VOCATIONAL HIGH SCHOOL IN PANGKAL PINANG - Arnida, Chandra (2014)
Speaking is an important aspect in language learning assisting people to convey ideas and maintain social relationship with others. However, some students are still unable to speak English fluently although they have learned it for many years. Thus, this study aims to investigate whether Communicative Language Teaching (CLT) is effective to improve the students' speaking ability. This study also aims to find out the students' responses to the implementation of CLT. This study involved two classes of second-grade-accountant students by employing a quasi-experimental design at one vocational high school in Pangkalpinang. The students were categorized into two: control and experimental groups. The data for this study were obtained from tests and a questionnaire which were analyzed quantitatively. The data from the tests were analyzed based on the components of speaking (Hadley, 2001), including accuracy, fluency, vocabulary, and pronunciation by using IBM SPSS statistics Version 16. Furthermore, the data from the questionnaire were analyzed by using Likert scale. The results of this study reveal that Communicative Language Teaching was effective to improve the students' speaking ability. The effectiveness was seen from the progress of the students' scores between the pre-test and the post-test. The progress was 5.35 points in which the mean score of the pre-test was 73.71 and the mean score of the posttest was 79.06. The results of this study also indicate that the students showed their positive responses to the implementation of CLT by the mean score of 3.45 out of 4. In conclusion, pedagogically, the results may encourage the teachers in the research site or in the other sites to implement this method as one of the beneficial ways in increasing the students' speaking ability, particularly in vocational high school level. Furthermore, theoretically, the results of this study contribute to the enrichment of the theories about the implementation of Communicative Language Teaching in teaching speaking. Moreover, it is suggested that the future researchers conduct advanced research related to the use of Communicative Language Teaching in teaching speaking.